The role of war-related industries in Russia's recent economic recovery - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
We construct a proxy for Russia's war-related output to evaluate the macroeconomic importance of war-related branches for Russia since the 2022 invasion of Ukraine. Our results suggest that warrelated branches contributed significantly to Russia's economic recovery after the sharp decline of GDP in spring 2022. The largest contribution came from low-tech industries where Russia is less dependent on imports. With war-related branches diverting resources from civilian industries, Russia will find it increasingly difficult to maintain its current level of growth.
urn:nbn:fi-fe20231213153778
Keywords: 330; Russia; economy; military industry; sanctions